Tax Exemption Goods Trade On ASEAN Free Trade Area (AFTA) According To Islamic Economics - Rahmania Nurul Fitri Amijaya; Andi Triyawan (University of Darussalam Gontor, 2018)
The Aim of this research is to determine the mechanism of tax exemption goods trade on ASEAN Free Trade Area (AFTA). This research also aims to determine the tax exemption goods trade on ASEAN Free Trade Area (AFTA) according to Islamic Economics. The type of research is qualitative research with critical study which is used the books, journals, and magazines of her writing. The research is giving the critical to the tax exemption goods trade according to Islamic economics which guided on Holy Qur'an, Prophetic Tradition, and some Moslem scholars. The mechanism from tax exemption goods trade on ASEAN Free Trade Area (AFTA) used Common Effective Preferential Tariff (CEPT) scheme with some programs as follows by inclusion list (IL), temporary exclusion list (TEL), sensitive list (SL), general exception (GE). Whereas, tax exemption goods trade on ASEAN Free Trade Area (AFTA) according to Islamic Economics is something rejected with the principles of Islamic Economics. In addition, Islamic Econmics applied ‘ushr on trading between countries and there are some requirement for every country pay ‘ushr depend on the prevail regulation.